Web design for dummies - Lopuck, Lisa (--For dummies., 2012)
Build your own eye-popping site designCreate a user-friendly site, design great graphics, and make updating easyIt can take a flock of folks to build, design, and maintain an out-of-sight Web site. Whether you're designing a site on your own or are a member of a design team, this updated guide will be your best assistant.